STADIUM HIV-AIDS TERHADAP PSYCHOLOGICAL WELLBEING DI KDS TOP KEDUNGDORO: Bahasa Indonesia - Gabriel Sinawang; Annastasia Putu Martha; Ni Ketut Suadnyaani (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2025)
Health-risk behaviors are often experienced by adolescents, such as drug use, or sexual risk behavior. Adolescents with chronic illnesses are at greater risk for mental health conditions because of their lives, stigma, discrimination or exclusion, or lack of access to quality support and services. Based on this description, it is still necessary to conduct a deeper identification of the HIV/AIDS stage conditions related to psychological wellbeing conditions. Method: The subjects of the study were 26 members of KDS TOP Kedungdoro who met the inclusion criteria. HIV stage 1-4 according to WHO. Psychological Wellbeing assessment used the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) questionnaire. Results: The results of the Spearman Rank analysis showed that there was no Sig. (2-tailed) value of 0.000. Because the Sig.(2-tailed) value > 0.05 means that there is no significant relationship between the two variables, namely the HIV-AIDS stage variable and the Psychological Wellbeing variable. The conclusion of the results of this study shows that there is no relationship between the HIV-AIDS stage and Psychological Wellbeing. Recommendations from the research results are expected to be able to conduct further research with a more adequate number of respondents so that the data obtained is more diverse and can conduct research to explore the factors that influence the HIV-AIDS stage and factors that influence Psychological Wellbeing such as quality of life, knowledge related to HIV and stigma experienced by respondents.